(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In this article, the authors comprehensively examine the history of the development and transformation of futurology as a scientific discipline. The purpose of the study is to reveal and briefly characterize the key ideas, concepts and events of the main stages of the development of futurology. Futurology in general is a generalized name for a set of concepts about the future of the planet, humanity, processes and phenomena based on scientific knowledge and forecasts. It is often understood as “the history of the future” or, as O. Fletheim proposed, “the philosophy of the future”, which will be an alternative to ideologies. Futurology is a multifaceted and interdisciplinary field of study, and there are many different theoretical approaches within it. It remains an important tool for analyzing and understanding the future and for developing strategies for a sustainable and positive future.